Pengaruh Manajemen Program Keterampilan Tehadap Pembinaan Minat Dan Bakat Siswa Untuk Mewujudkan Hasil Belajar Siswa - Nurani Dewi, Rani; Ainissyifa, Hilda; Zuhri, M. Tajudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of Skill Program Management on the Development of Students’ Interests and Talents and its implications for Student Learning Outcomes at MAN 1 Garut. This research employed a quantitative approach using a causal associative method. The population consisted of all teachers at MAN 1 Garut, totaling 76 respondents, with a saturated sampling technique. Data were collected through Likert-scale questionnaires, observation, and documentation. Data analysis was conducted using path analysis to examine both direct and indirect effects among variables. The results indicate that Skill Program Management has a significant effect on the Development of Students’ Interests and Talents, contributing 52.1%. Skill Program Management also significantly affects Student Learning Outcomes with a contribution of 34.2%, while the Development of Interests and Talents contributes 47.8% to Learning Outcomes. The indirect effect of Skill Program Management on Learning Outcomes through the Development of Interests and Talents is greater than its direct effect, indicating a strong mediating role. These findings demonstrate that well-planned, organized, and student-oriented skill program management can effectively enhance student learning outcomes within the framework of Islamic Education Management.